EFL Teachers’ Beliefs In Teaching Writing Through The TPACK Framework - Sri Mila Sari; Yogi Setia Samsi; Dayat Hidayat (INTERACTION: Jurnal Pendidikan Bahasa, 2023)
Covid-19 has caused changes in learning activities. Teaching and learning activities that were previously face-to-face have changed to distance learning that requires technology. Unfortunately, not all teachers have sufficient competence regarding technology integration in teaching. Therefore, a knowledge concept called TPACK emerged, which can help improve teacher competence in technology. The TPACK framework is believed to help teachers design teaching activities that can stimulate, motivate, and make students more active because they are facilitated by technology. However, several factors can hinder teachers from integrating technology into teaching, one of which is the teacher’s beliefs. Therefore, the researchers focused on exploring teachers’ beliefs in teaching writing through the TPACK framework. The research was conducted at one of the Klari Karawang Middle Schools involving two EFL teachers. Data were obtained through interviews, observation, and documentation. The results of this study found that six factors shape teachers’ beliefs in teaching writing through the TPACK framework. In addition, the beliefs they profess are reflected in their teaching practices.